THE ADULT RESPONSIBILITIES AS THE TRIGGER FACTOR OF PSYCHOLOGICAL CONFLICTS IN THE MOVIE 30 GOING ON 30 BY GARRY WINICK - Rizky, Rara; Hafsah, Siti (Faculty of Letters Universitas Balikpapan, 2026)
This research discusses how adult responsibilities trigger psychological conflicts in the movie 13 Going on 30 by Garry Winick. There are two objectives for the purpose of this: To identify the forms of adult life responsibilities found in the movie 13 Going on 30 by Garry Winick and to describe adult responsibilities trigger psychological conflict in the movie 13 Going on 30 by Garry Winick. This research uses psychology of literature with coverage Psychosocial Development by Erik Erikson and Field Theory by Kurt Lewin because the theories is relevant to addressing the Adult Responsibilities trigger Psychological Conflict. The researcher used qualitative methods that is explained descriptively based on this research using document analysis as a reference. The finding of this research found 2 form of Adult Responsibilities with 33 data on Intimacy vs. Isolation and 26 data on Generativity vs. Stagnation. Then through the adult responsibilities as the trigger factor of psychological conflict represent the Approach-approach conflict with 21 data, Approach-avoidance conflict with 34 data, and Avoidance-avoidance conflict with 6 data. The findings reveal that the most dominant form of adult responsibility in the movie 13 Going on 30 is embracing emotional vulnerability, which frequently emerges within an approach-avoidance conflict.